"Well, there's a more scientific way to do it!": factors influencing receptivity to evidence-based practices in police organizations. (1st November 2020) - Kalyal, Hina
ABSTRACT: Evidence-based policing (EBP) is a decision-making perspective noted for its effectiveness in enhancing organizational performance. However, police in North America have been rather slow in adopting such practices. Few attempts have been made to understand how police organizations become receptive towards EBP. Based on 38 in-depth interviews with police executives and senior civilian officers across Canada, and utilizing a model of innovation adoption, the present study examines how openness towards EBP develops in police organizations. The results highlight a number of factors in the agency's external and internal environment that enhance receptivity to a decision-making perspective based on scientific evidence.